Optimized Animal Model of Cyclophosphamide‐induced Bone Marrow Suppression. Issue 5 (27th May 2016) - Feng, Lizhi; Huang, Qiuju; Huang, Zhiying; Li, Hang; Qi, Xiaoxiao; Wang, Ying; Liu, Zhongqiu; Liu, Xiaohong; Lu, Linlin
Abstract: Myelosuppression is one of the serious side effects of anticancer chemotherapeutic drugs that deteriorate the bodily functions of patients, thereby affecting the quality of life considerably. Prevention of myelosuppression in anticancer chemotherapy is an important research topic. A stabilized chemotherapy‐induced myelosuppression animal model is necessary in experimental research. This study aimed to establish an optimized animal model of chemotherapy‐induced bone marrow suppression. After C57BL/6 mice were treated with intermediate‐ and high‐dose (25/50 mg/kg) cyclophosphamide (CTX) for 10 days, the body‐weight, changes in thymus and spleen, number of white blood cells (WBCs), red blood cells (RBCs), and platelets (PLTs) and changes in bone marrow in the mice were systematically evaluated at the next 2, 7 and 14 days. Our results demonstrated that CTX treatments could significantly decrease the body‐weight of mice, as well as the ratios of the weights of thymus and spleen to body‐weight. The physiological structures of thymus and spleen were destroyed by CTX treatments. The number of WBCs and RBCs significantly declined after CTX treatments; however, the number of PLTs increased. Moreover, the expression of Sca1 in bone marrow cells decreased on Day 2 but increased on Day 14. The expression of CD34 decreased in bone marrow cells after CTX treatments. In conclusion, mice models, with high‐dose CTX treatments for 10 days, can be an optimized animal model for chemotherapy‐induced bone marrow suppression.